Geological Heritage Site for the Rajmahal Flora at Mandro, Sahibganj, India: An Opportunity for an Integrated–Sustainable Tourism Circuit - Shreya Shrey; Ravi Shankar Chaubey; Pankaj Jaiswal (Geoconservation Research)
Mandro in Sahibganj District of Jharkhand State, India is known for its abundance of petrified wood and floral impressions from the Rajmahal Traps of Albian–Aptian age. This locality is among the 34 Geological Heritage Sites identified by the Geological Survey of India. The scientific importance of the site is vested in the intricate preservation of petrified wood and floral impressions in a single locality. The plants were transported by pyroclastic volcanic activity, and the tuff and crystal-laden pumice helped preserve the fossils, including upright tree stumps with intact root systems. Such an association of floral fossils with ignimbrite is of high scientific relevance and is one of its kind in India. At present, the Geoheritage Site, Mandro is compromised by the lack of legislative provisions guiding conservation of the site. Our study highlights bottlenecks in the development of the Geoheritage Site and suggests the formulation of an integrated–sustainable tourism circuit combining natural, anthropological, cultural and historical touristic components. We advocate operating the circuit through community participation, ensuring trust and capacity building among the local People. The circuit is an exclusively local tourism engine that could address socioeconomic disparities while developing as a hub for research and innovation across different disciplines. Paramount to these efforts is attaining Sustainable Development Goals and global recognition for the Geoheritage Site and the Circuit.